Eremanthus arboreus (Gardner) MacLeish (Candeeiro): natural source of α-Bisabolol (Research, Society and Development, 2020)
There is a growing search in the chemical composition of essential oils, as they have biological and pharmacological activities. Among the plants with homogeneous composition in essential oils stands out the species Eremanthus arboreus (Gardner) MacLeish, (Asteraceae) popularly known as the “candeeiro”. This plant species is native to Chapada of Araripe - Ceará, Brazil. The objective was to characterize chemically the constituents of the essential oil (OE) of E. arboreus by means of Gas Chromatography and perform a review of its biological and pharmacological activities. The botanical material was collected in Chapada of Araripe, Barbalha - CE, Brazil, in April 2014, the extraction and collection of OE was done in Clevenger apparatus. The chemical composition of the OE was performed by Gas Chromatography coupled to Mass Spectrometry (CG/MS). As for the review, specialized scientific bases (Scopus, Scielo and Web of Science) were consulted. According to the results, 8 constituents were identified, where α-Bisabolol is mentioned as being the main component of the essential oil of this species. As for the biological and pharmacological activities of the OE, it was demonstrated that the species has the following activities: antimicrobial, larvicide, anti-inflammatory and antinociceptive. Eremanthus arboreus is a species with great pharmaceutical potential and also an alternative for industries that target products based on the constituent α-Bisabolol.